Analysis of the Effect of Service Quality and Patient Satisfaction on Patient Compliance Level in the Medical Rehabilitation Polycle of UMM Hospital - Elsa Fian Dennis Alfandy; Sentot Imam Suprapto; Ratna Wardani (Journal Public Health and Clinical Science, 2026)
Patient satisfaction is one of the first indicators of hospital standards and measures of service quality. Low patient satisfaction will affect hospital visits, patient satisfaction is determined by the quality of service provided to patients where patient demands and service quality will increase over time and have an impact on the level of patient compliance. The purpose of this study is to analyze the effect of service quality and patient satisfaction on patient compliance at the Medical Rehabilitation Polyclinic of UMM General Hospital. In this study, researchers used an analytical quantitative design with a cross-sectional approach. The population in this study were outpatients at the Medical Rehabilitation Polyclinic of UMM General Hospital in August 2025, amounting to 988 patients, the number of research samples was determined by the Krejcie & Morgan table so that the number of samples was determined as 270 respondents. The data analysis technique used path analysis. The results of the analysis can be seen that there is an influence of service quality on patient satisfaction at the Medical Rehabilitation Polyclinic of UMM General Hospital, meaning that with better service quality, patient satisfaction will increase. There is an influence of service quality on patient compliance in the Medical Rehabilitation Clinic, meaning that with better service quality, patient compliance in the Medical Rehabilitation Clinic will increase. The results of the analysis show the influence of patient satisfaction on patient compliance in the Medical Rehabilitation Clinic, meaning that with increasing patient satisfaction, patient compliance will increase. Patient satisfaction has been proven to be an intervening variable in the influence of service quality on patient compliance in the Medical Rehabilitation Clinic. These results indicate that with increasing patient satisfaction, the influence of service quality on patient compliance can increase.